Molecular Identification of Rhizosphere Trichoderma spp. and Their Antagonistic Impact Against Some Plant Pathogenic Fungi (Baghdad Science Journal, 2016)
The main aim of this study was to molecular identification and determine the antagonistic impact of rhizosphere Trichoderma spp. against some phytopathogenic fungi, including (Magnaporthe grisea) pyricularia oryzae, Rhizoctonia solani and Macrophomina phasolina. Four Trichoderma isolates were isolated from rhizosphere soils of the different host plants in different locations of Egyptian governorates. The morphological characterization of isolated Trichoderma as well as using of (ITS1-5.8S-ITS2) ribosomal gene sequence acquisition and data analyses. By comparing the results of DNA sequences of ITS region, the fungi represented one isolate were positively identified as T. asperellum (1 isolate T1) and one as T. longibrachiatum (1 isolate T2) and two as Trichoderma harzianum (2 isolates T3 and T4). The results showed similarity value of (5.8S-ITS) region sequence of the two isolates, T1 (T. asperellum) and T2 (T. longibrachiatum) of (99%, 99%), respectively. The similarity value of (5.8S-ITS) region sequence with isolates of T3, T4 (T. harzianum) of (99%). On the other side, the results of molecular identification of phytopathogenic fungi represented high similarity value of (5.8S-ITS) region sequence and were identified as P.oryzae, R. solani and M. phasolina (99, 96 and 99%) respectively. Variations and genetic relationships among 4 Trichoderma isolates were investigated by using the Rapid Amplification of Polymorphic DNA (RAPD) profiles using ten random primers. All Trichoderma isolates were assessed for their antagonistic impact on phytopathogens P. oryzae, R. solani and M. phasolina. Though T. harzianum isolates were more affects than T. longibrachiatum and T. asperellum isolates, the percent inhibitory effect among T. harzianum isolates were vary much (44.8 to 91.6%). The inhibitory effect of T. asperellum isolates ranged from 42.2 to (86.0%), while T. longibrachiatum exhibiting affect ranged between (47.5%) to (83.8%).